Li depletion in solar analogues with exoplanets: Extending the sample - Mena, E. Delgado (2013)
We want to study the effects of the formation of planets and planetary systems on the atmospheric Li abundance of planet host stars. In this work we present new determinations of lithium abundances for 326 Main Sequence stars with and without planets in the T$_eff$ range 5600-5900 K. 277 stars come from the HARPS sample, the remaining targets have been observed with a variety of high resolution spectrographs. We confirm significant differences in the Li distribution of solar twins (T$_eff$ = T$_{\odot} ±$ 80 K, log g = log g$_{\odot}$ $±$ 0.2 and [Fe/H] = [Fe/H]$_{\odot} ±$ 0.2): the full sample of planet host stars (22) shows Li average values lower than "single" stars with no detected planets (60). If we focus in subsamples with narrower ranges in metallicity and age, we observe indications of a similar result though it is not so clear for some of the studied subsamples. Furthermore, we compare the observed spectra of several couples of stars with very similar parameters which show different Li abundances up to 1.6 dex. Therefore we show that neither age, nor mass nor metallicity of a parent star is the only responsible for enhanced Li depletion in solar analogues. We conclude that another variable must account for that difference and suggest that this could be the presence of planets which causes additional rotationally induced mixing in the external layers of planet host stars. Moreover, we find indications that the amount of depletion of Li in planet host solar-type stars is higher when the planets are more massive than Jupiter.